In situ synthesis of ligand reduced/capped silver nanoparticles and the effect of temperature and ligand structure on the size of silver nanoparticles - Kasture, M. B.; Patel, P.; Prabhune, Asmita; Ramana, C. V.; Kulkarni, A. A.; Bhagavatula L. V. Prasad (Journal of Chemical Sciences, 2008)
We report in situ synthesis of silver nanoparticles using biosurfactants called sophorolipids as reducing and capping agents. We further study the effect of temperature and the structure of sophorolipid on the size of silver nanoparticles obtained. The silver nanoparticles were characterized by UV-visible, transmission electron microscope (TEM) and light scattering (DLS) analysis techniques.
Keywords: dynamic light scattering; Nucleation and growth; silver nanoparticles; Sophorolipid

Impinging jet micromixer for flow synthesis of nanocrystalline MgO: role of mixing/impingement zone - Kumar, D. V. Ravi; Bhagavatula L. V. Prasad; Kulkarni, A. A. (Industrial & Engineering Chemistry Research, 2013)
Continuous flow synthesis of nanomaterials via sol-gel process using microreactors has not received much attention. For the synthesis of gels where the reaction time is of the order of few seconds to few tens of seconds, microchannel reactors are an excellent processing option. However since a `gel' does not `flow' easily, making it in a microchannel usually clogs the microchannel. We envisaged that by using an impinging jet micromixer, where the two reactants impinge and collide to form a mixing zone outside the micromixer, this problem could be circumvented. Here we report a successful implementation of continuous flow synthesis of metal oxides formed by the rapid sol-gel process taking the nanocrystalline MgO (NC-MgO) as a specific example. Furthermore, we clearly demonstrate that the nature of the mixing zone formed by the impinging jets governs the surface area of the product. Specific flow rate and impingement angle are identified that yield high surface area materials.